2017
DOI: 10.1039/c7ra10045k
|View full text |Cite
|
Sign up to set email alerts
|

Piperidinium-based ionic liquid electrolyte with linear solvent and LiODFB for LiFePO4/Li cells at room and high temperature

Abstract: Lithium difluoro(oxalato)borate (LiODFB) combines the advantages of the salts LiBOB and LiBF4 when used in electrolytes for lithium ion cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…8d, the B 1 s presents two prominent peaks, locating at about 191.00 eV and 192.42 eV, which is attributed to the B-O of LiDFOB. 36 This further confirms that the LiDFOB can decompose and produce an artificial CEI layer, which can effectively inhibit the decomposition of LiPF 6 and improve the stability of the NCM811 cathode. In this paper, all these data suggest that the addition of LiDFOB could form a protective film during the cycling of NCM811 cathode at 60 °C, which endows a good electrochemical performance of the cells at high temperature.…”
Section: Resultssupporting
confidence: 56%
“…8d, the B 1 s presents two prominent peaks, locating at about 191.00 eV and 192.42 eV, which is attributed to the B-O of LiDFOB. 36 This further confirms that the LiDFOB can decompose and produce an artificial CEI layer, which can effectively inhibit the decomposition of LiPF 6 and improve the stability of the NCM811 cathode. In this paper, all these data suggest that the addition of LiDFOB could form a protective film during the cycling of NCM811 cathode at 60 °C, which endows a good electrochemical performance of the cells at high temperature.…”
Section: Resultssupporting
confidence: 56%
“…The C 1s spectra of the pristine contain three peaks, and these peaks correspond to C-C (284.8eV), C-H (285.7eV) and C-F (291.1eV) in PVDF. [32][33][34] The F 1s spectra only have a single peak at 687.8eV (C-F) which is assigned to PVDF. 35 New peaks appeared on the surface of the cathode with different electrolyte after 100 cycles including C-O (286.4eV), C=O (288.9eV) and Li-F (685.2eV).…”
Section: Resultsmentioning
confidence: 99%
“…The peaks of NCM811 with E0 at 167.8 eV and 168.7 eV are corresponded to Li 2 SO 3 and ROSO 2 Li which are derived from SL. 33,39,40 It represents that IL and SL participate in the modification of CEI layers.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23] ILs have been used as promising electrolyte additives in the high voltage LIBs due to the advantages of thermal stability, non-ammability and large electrochemical window. [24][25][26][27][28] Piperidinium-based ILs are gradually used as electrolyte additives in LIBs due to high conductivity and wide electrochemical window. Dong, et al have revealed that a piperidium-based IL is used in high voltage and temperature conditions, the addition of IL results in the formation of a protective cathode lm inhibiting severe decomposition of electrolytes.…”
Section: Introductionmentioning
confidence: 99%